High proportion of PD‐1‐expressing CD4+ T cells in adipose tissue constitutes an immunomodulatory microenvironment that may support HIV persistence. Issue 12 (28th August 2017) - Damouche, Abderaouf; Pourcher, Guillaume; Pourcher, Valérie; Benoist, Stéphane; Busson, Elodie; Lataillade, Jean‐Jacques; Le Van, Mélanie; Lazure, Thierry; Adam, Julien; Favier, Benoit; Vaslin, Bruno; Müller‐Trutwin, Michaela; et al.
Abstract: We and others have demonstrated that adipose tissue is a reservoir for HIV. Evaluation of the mechanisms responsible for viral persistence may lead to ways of reducing these reservoirs. Here, we evaluated the immune characteristics of adipose tissue in HIV‐infected patients receiving antiretroviral therapy (ART) and in non‐HIV‐infected patients. We notably sought to determine whether adipose tissue's intrinsic properties and/or HIV induced alteration of the tissue environment may favour viral persistence. ART‐controlled HIV infection was associated with a difference in the CD4/CD8 T‐cell ratio and an elevated proportion of Treg cells in subcutaneous adipose tissue. No changes in Th1, Th2 and Th17 cell proportions or activation markers expression on T cell (Ki‐67, HLA‐DR) could be detected, and the percentage of CD69‐expressing resident memory CD4 + T cells was not affected. Overall, our results indicate that adipose‐tissue‐resident CD4 + T cells are not extensively activated during HIV infection. PD‐1 was expressed by a high proportion of tissue‐resident memory CD4 + T cells in both HIV‐infected patients and non‐HIV‐infected patients. Our findings suggest that adipose tissue's intrinsic immunomodulatory properties may limit immune activation and thus may strongly contribute to viral persistence. Abstract : Adipose tissue CD4 T cells exhibit a tissue‐specific profile defined by high expression of PD‐1. The functional relevance of such high PD‐1 expression on adipose CD4 T cells remains unclear but it may favor HIV persistence since PD1 expressing CD4 T cells has been described as a preferential HIV reservoir.